Maths
posted by Neee on .
Solve the given equation:
ln(x + 4) + ln(x + 2) = 2
ps  we aren't allowed calculators
My ans:
I got as far as
ln [(x+4)(x+2)] = 2
ln (x^2+6x+8) = 2
And then I am lost, whatever I do ends up with no answer.
I also rewrote the above so that it is
e^2 = x^2+6x+8
But of course that made it worse :(

I am also stuck just as you are.

i also got the same equation:
ln [(x+4)(x+2)] = 2
ln (x^2+6x+8) = 2
x^2+6x+8 = e^2
x^2+6x+(8e^2)=0
thus, you have no choice but to use quadratic formula: (where a=1, b=6, c=8e^2)
[6+sqrt(6^24(1)(8e^2))]/2(1)
[6+sqrt(3632+4e^2)]/2
[6+sqrt(4+4e^2)]/2 *factor out 4
[6+2(sqrt{1+e^2})]/2
therefore, x is equal to:
3+sqrt(1+e^2) and 3sqrt(1+e^2)
so there,, =)